Pemodelan Sistem Infomasi Keuangan Sekolah Menggunakan Model User Experience Design - Purbha Irwansyah, Irsyad; Damuri, Amat; Yudaningsih, Nunik (TEMATIK, 2022)
The school financial information system if managed very well will be an advantage in the implementation of activities and become a good spearhead for an educational institution. The current problem of processing school financial administration data is ineffectiveness and efficiency in the processing of school financial data, so it greatly affects the speed in determining a decision by high-level school management. The purpose of this research is the application of the user experience design model in making the modeling of the school financial information system very effective which folds system users in every system design starting from the stages of understand, research, sketch, design, implementation, and evaluate. The results of the school financial information system modeling test using a user experience design model for testing system functionality using blackbox testing got a value of 100% according to the functionality of the system, and the test results of Web Quality 4.0 got a value of 87.69% having excellent criteria from usability testing conducted on users.